Integrated pharmacokinetic–pharmacodynamic analysis of macrocyclic lactones in sheep infested with resistant Psoroptes ovis - Herrera, Rodolfo; Miró, Maria Victoria; Lifschitz, Adrian Luis; Larroza, Marcela Patricia (Elsevier, 2026)
The current study aimed to investigate the pharmacokinetic/pharmacodynamic (PK/PD) relationship of five macrocyclic lactone (MLs) formulations, three 1 % formulations (ivermectin, doramectin and moxidectin) and two long-acting 3.15 % products (ivermectin and doramectin), against sheep experimentally infested with resistant Psoroptes ovis under standardized doses. Thirty naïve Merino sheep were experimentally infested and randomly assigned to five treatment groups (n = 6). Baseline mite counts were not used to block animals during group allocation. The three 1 % formulations of ivermectin (IVM), doramectin (DRM), and moxidectin (MXD), were administered off-label at a dose of 0.5–0.6 mg/kg on days 0 and 7, subcutaneously. The long-acting 3.15 % formulations were subcutaneously administered once at their approved doses of 1.05 mg/kg (IVM 3.15 %) and 1.26 mg/kg (DRM 3.15 %). Plasma drug concentrations and mite counts were assessed between 0 and 35 days post-treatment. Conventional 1 % formulations produced higher peak plasma concentrations than long-acting formulations, although the latter showed greater persistence, similar to that observed with repeated MXD 1 %. DRM 1 % showed greater systemic exposure compared to 3.15 % long acting formulations and IVM 1 %. Significant reductions in mite counts were observed by day 7 with DRM 1 %, and by day 14 with IVM 1 % and MXD 1 %. In contrast, long-acting formulations showed delayed responses, with significant reductions only by day 21. Only DRM 1 % and MXD 1 % achieved 100 % efficacy. PK/PD indices established for ML-resistant P. ovis were calculated as the ratio between peak plasma concentration (Cmax) and the minimal inhibitory concentration (MIC) values of 15 and 30 ng/mL (Cmax/MIC), as well as the ratios between the area under the concentration–time curve (AUC) and the same MIC values (AUC/MIC). The Cmax/MIC ratio observed for 1 % formulations were significantly higher compared to those obtained with the long-acting formulations at both MIC levels. For the AUC/MIC parameter, the 1 % formulations exhibited significantly higher values compared to the long-acting formulations for the MIC 30 ng/mL.These findings suggest that both the magnitude and duration of MLs in plasma are critical for efficacy against P. ovis.